Motivations and cognitive models associated with decentralized seed multiplication: Experiences from biofortified sweetpotato vine multipliers in Kenya and Ethiopia - Okello, J.J.; Jogo, W.; Kwikiriza, N.; Muoki, Penina Ngusye (Emerald Publishing Limited, 2018)
The purpose of this paper is to examine the structure and content of mental models associated with the decision to engage in biofortified sweetpotato vine multiplication as a business. The study focused on decentralized vine multipliers from Kenya and Ethiopia. These were stratified by orientation toward nutrition or commercial value addition. A total of 45 multipliers were interviewed. Means-end chain (MEC) analysis combined with laddering technique was used to generate mental constructs multipliers relate with the decision to engage in biofortified sweetpotato vine multiplication. The structure and content of mental models of biofortified sweetpotato vine multipliers supporting nutrition-focused interventions and those supporting commercial value-addition sweetpotato interventions are different. Nutrition-focused multipliers are driven by the benefits of good health, while commercial value-addition interventions are driven by the benefit of making “more money.” The content and structure of mental models are also country/region specific. This study has demonstrated that decision to engage in community seed production business is driven not only by the desire to make profits but, equally importantly, by personal and societal (social) factors. It has also discussed the limitations of current analysis and future research areas.